Multi-Technology Positioning - Nurmi, Jari.; Lohan, Elena-Simona.; Wymeersch, Henk.; Seco-Granados, Gonzalo; Nykänen, Ossi.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book provides an overview of positioning technologies, applications and services in a format accessible to a wide variety of readers. Readers who have always wanted to understand how satellite-based positioning, wireless network positioning, inertial navigation, and their combinations work will find great value in this book. Readers will also learn about the advantages and disadvantages of different positioning methods, their limitations and challenges. Cognitive positioning, adding the brain to determine which technologies to use at device runtime, is introduced as well. Coverage also includes the use of position information for Location Based Services (LBS), as well as context-aware positioning services, designed for better user experience. • Brings understanding of positioning technology to readers from a variety of disciplines • Reviews multiple techniques, providing insight on the pros, cons and challenges related to each • Designedto be a tutorial on basic principles, avoiding unnecessary detail • Offers lessons learned from a cross-sector international network, from both academic and industrial perspective and from a multi-cultural view.
Introduction and book structure -- MULTI-POS - multi-technology positioning professionals training network -- Understanding the Global Navigation Satellite System (GNSS) Signal Model -- GNSS Vulnerabilities -- GNSS Quality of Service in urban environment -- Multi-GNSS: facts and issues -- Towards Seamless Navigation -- Mapping the radio world to find us -- Survey on 5G Positioning -- Formation Control of Multi-agent Systems with Location Uncertainty -- Positioning Technology Applications Related to Environmental Issues -- Context awareness for semantic mobile computing -- The Impact of Galileo Open Service on Location Based Services Markets -- Location Based Services analysis through Analytical Hierarchical Processes - an e-health-based case study -- DroneAlert: Autonomous Drones For Emergency Response -- MULTI-POS - Lessons learnt from fellows and supervisors -- Conclusions -- About the editors.
Keywords: Electronic circuits; Signal processing; Computer networks .; Geographic information systems; Electronic Circuits and Systems; Signal, Speech and Image Processing; Computer Communication Networks; Geographical Information System